Plan de mercadeo de una empresa de servicios de consultoría técnica e innovación para la industria alimentaria - Rojas-Quesada, Adriana; Valverde Moya, José Antonio (Instituto Tecnológico de Costa Rica, 2018)
INFOOD is a knowledge company addressed to the Assistance and Innovation with a personal service toward the micro, small and medium companies (MIPYMES in Spanish) in the areas of production, development of products and commercialization of the food industry in Costa Rica. As a new company, it does not have a defined market or a strategic service to give. It waits until businesses opportunities come and needs this Marketing Plan whose purpose is the planning and recruitment of clients through the offer of technical services and innovation in the food industry of the country. These clients are obtained through a promotional strategy of ATL in interactive media in order to generate electronics emails and a Web page. As part of its BTL campaign, INFOOD is going to participate in events of the food industry such as local and expo parades (EXPOCACIA in Spanish) with stands to promote its consulting service. MIPYMES are clients of relatively easy access that urgently need an external consulting company to help in the solution of specific problems and the generation of new opportunities with creativity and innovation, because they do not have a Research and Development (I&D in Spanish) department to do it by themselves. The personal service that the founders have been offering let them to create a very close relationship with its clients in an atmosphere of confidence and fidelity. This experience is strength through the capacitation of its employees in order to keep a good relationship with the clients (CRM) improving the culture of fidelity with common and potential clients.
Proyecto de Graduación (Maestría en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2018.
Keywords: Consultoría; Creatividad; Calidad; MIPYMES; Negocios